College adjustment and student-life stress as factors affecting student success of the pioneer K-12 graduates - Braga, Ann Christine V. (College of Education, University of the Philippines Diliman, 2021)
The Philippines was among the last countries in the ASEAN region to implement the K-12 curriculum, with its first batch of students graduating last March of 2018. This educational shift is expected to have produced not only academically-prepared but also more matured college students. Given its recency, there is a dearth of local studies on the K-12 graduates, which makes this study both timely and of relevance. This mixed-methods research investigated how the batch of the K-12 graduates are faring in the University setting. Specifically, it quantified the College Adjustment, Student-Life Stress and Student Success of 400 respondents using the College Adjustment Questionnaire (CAQ), Student-Life Stress Inventory (SSI) and the Academic Success Inventory for College Students (ASICS) respectively. Moreover, it measured the relationship between college adjustment and student-life stress, and if these two variables could affect students' grades (GWA) and student success. Participants reported to have a moderate level of college adjustment and student success, but a high level of student-life stress. Quantitative analysis indicated there is a weak, inverse relationship between college adjustment and student-life stress, implying that as students achieve adjustment into the university setting, the less frequently they encounter stressors. Furthermore, both these variables can also affect grades (GWA) and student success. These results are also supplements by focus group discussions, specific experiences and ideas of students in relation to their adjustment, stressors and reactions to these stressors.